Sistem Monitoring Tingkat Kekeruhan Air dan Pemberi Pakan Otomatis pada Kolam Budidaya Ikan Koi Berbasis NodeMCU - Putrawan, I Gede Hery; Rahardjo, Pratolo; Agung, I G A Putu Raka (Majalah Ilmiah Teknologi Elektro; Vol 19 No 1 (2020): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i01.P01, 2019)
Nowadays, many Indonesian people working as a fish cultivator. This is  because the turnover obtained from the sale of fish, one of which is koi fish is quiet high. To cutivate fish especially koi fish, ultivators will make many pools to cultivate these fish. From the first is spawning pool, tiller fish pool and brood pool. To get good quality cultivation, the pools must always be clean (has a turbidity level of water < 400 NTU). Therefore, a system was created to be able to monitor the water turbidity level and automatic feed in koi fish pool which the purpose is helping koi fish cultivator improve their cultivation quality. The monitoring system of the cultivation pool turbidity level works by reading the turbidity value of the pool using a turbidity sensor (Turbidity Sensor). The reading of the sensor value will be processed by the NodeMCU microcontroller and then activate the drainage pump relay module for which will drain turbid water. On the other hand there is a proximity sensor that will measure the height of the pool water. When the pool water is drained, the proximity sensor will send a signal to the NodeMCU microcontroller to activate the distribution pump relay module, so that it can distribute clean water from the water tank to the pool. Therefore, the cultivation pool’s water always be clean. Meanwhile, automatic feeders work using the RTC (Real Time Clock) module in which the feeding time will be set in this module. Then, the time output from the RTC module will be processed by the NodeMCU microcontroller which then sends a signal to the servo as the drive for the fish feed lever. When it is time for feeding, according to the program provided the fish feed lever will open. Therefore, feeding can be done automatically. Keywords — IoT, monitoring, turbidity, feeder, koi fish, cultivation pools.